Eleştirel düşünme kuramının lise coğrafya programı üzerindeki etkileri - Hilmi DEMİRKAYA (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
School geography has the potential to develop young people’s understanding of their place in the world and so help form their identity. Young geography teachers are therefore more likely to work with disillusioned and cynical older collagues than they were ten or twenty years ago. Schools and teachers are variously affected by recent attempts to redefine, restructure and repoliticize schooling, but in general it is becoming harder for geography teachers to work in ways which reflect progressive and radical ideals. The construction of the Geography National Curriculum was not without its critics and dissenters but the final product gives little indication of the relationship between geography and society and does little to advance teachers’ and pupils’ understanding of the threats and promises presented by disorganized capitalism. As far as the state is concerned, school geography should develop a multidimensional and multilayered form of citizenship which prompts a critical engagement with economic, political, social and cultural rights and responsibilities at local, national, regional and international scales